1997
DOI: 10.1002/(sici)1096-9861(19970428)381:1<68::aid-cne6>3.0.co;2-i
|View full text |Cite
|
Sign up to set email alerts
|

Transneuronal retinal input to the primate Edinger-Westphal nucleus

Abstract: The Edinger-Westphal nucleus of the oculomotor nuclear complex provides preganglionic parasympathetic innervation to the pupil. We labelled its retinal input by transneuronal autoradiography after an eye injection of [3H]proline in the macaque monkey. The primary retinal projection to the pretectum terminated in the ipsilateral and contralateral olivary nuclei. These nuclei were intensely labelled and sharply delimited, with a mean diameter of 590 microm and a rostrocaudal length of 2.52 mm. The caudal half of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 46 publications
2
34
0
Order By: Relevance
“…Trans-synaptic tracer experiments suggested that this nucleus receives retinal input by way of the pretectum (Kourouyan and Horton, 1997). The present study indicates the lvc is not part of EW PG , but is instead a satellite nucleus that receives bilateral pretectal input and projects back upon the contralateral pretectum, by way of the posterior commissure.…”
Section: Discussionmentioning
confidence: 50%
See 3 more Smart Citations
“…Trans-synaptic tracer experiments suggested that this nucleus receives retinal input by way of the pretectum (Kourouyan and Horton, 1997). The present study indicates the lvc is not part of EW PG , but is instead a satellite nucleus that receives bilateral pretectal input and projects back upon the contralateral pretectum, by way of the posterior commissure.…”
Section: Discussionmentioning
confidence: 50%
“…4C-G). We believe this structure is equivalent to the one termed the lateral visceral column (lvc) in previous studies (Kourouyan and Horton, 1997;Baleydier et al, 1990;Büttner-Ennever et al, 1996), and so have continued to use this term to identify it. The lvc appears to be connected to the contralateral pretectum by way of the posterior commissure (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Lesion studies in primates demonstrate the relevance of striate and extrastriate visual cortical areas for unperturbed slow eye movements and symmetric mhOKN (e.g., Ter Braak and Van Vliet, 1963;Lynch and McLaren, 1983;Zee et al, 1987;Dürsteler and Wurtz, 1988). As we failed to reveal a cortical input to the NOT-DTN at P9, binocularity in the NOT-DTN up to this age should indeed originate from the direct projections of retinal ganglion cells from both eyes (Ballas et al, 1981;Kourouyan and Horton, 1997;Telkes et al, 2000). However, already at P12 and P14, we could convincingly demonstrate a direct cortical projection to the NOT-DTN arising from V1 and even more strongly from MT which, however, did not increase binocular balance at once, i.e., a large proportion of neurons was still dominated by the contralateral eye.…”
Section: Maturation Of the Optokinetic Reflex And Not-dtnmentioning
confidence: 55%